2020
DOI: 10.1101/2020.03.10.985663
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Filamentous Bacteriophage Delay Healing of Pseudomonas-Infected Wounds

Abstract: We have identified a novel role for filamentous bacteriophage in the delayed healing associated with chronic Pseudomonas aeruginosa (Pa) wound infections. In a mouse model of chronic Pa-infected wounds, Pf, a filamentous phage produced by Pa, impaired keratinocyte migration, prevented wound reepithelialization, and delayed healing in both the absence and presence of live bacteria. Mechanistically, the immune response to Pf phage produces soluble factors that impair keratinocyte migration and delay wound re-epi… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…We observed that less than 10% of children with CF who are infected with Pa have Pf+ strains, while over 40% of adults and 100% of 10 pre-lung transplant patients have Pf+ strains (7). The prevalence of Pf phages likewise increases over time in patients with chronic Pa wound infections (42). Together these data point to selective advantages for Pf+ Pa strains in the setting of chronic infection.…”
Section: Introductionmentioning
confidence: 64%
“…We observed that less than 10% of children with CF who are infected with Pa have Pf+ strains, while over 40% of adults and 100% of 10 pre-lung transplant patients have Pf+ strains (7). The prevalence of Pf phages likewise increases over time in patients with chronic Pa wound infections (42). Together these data point to selective advantages for Pf+ Pa strains in the setting of chronic infection.…”
Section: Introductionmentioning
confidence: 64%
“…Filamentous phages infecting P. aeruginosa can physically interact with mammalian immune cells triggering a maladaptive immune response that results in impaired bacterial clearance during infections ( Sweere et al, 2019 ). These phages have been also involved in an immune response impairing keratinocyte migration and leading to delayed healing of P. aeruginosa -infected wounds ( Bach et al, 2020 ). Although filamentous phages do not represent a virus type selected for therapy purposes, these studies highlight the complex consequences of previously unknown interactions between phages and the immune system.…”
Section: Revisiting Phage Therapymentioning
confidence: 99%
“…Less than 10% of children with CF who are infected with Pa have Pf-positive (Pf+) strains, while over 40% of adults and 100% of 10 prelung transplant patients have Pf+ strains ( 7 , 26 ). The prevalence of Pf phages likewise increases over time in patients with chronic Pa wound infections ( 32 ). Of note, in a longitudinal cohort study of patients with CF, the acquisition of Pf phage represented the appearance of a new strain of Pa .…”
Section: Introductionmentioning
confidence: 99%